Parental support and perceived self-efficacy − a study of parental perceptions in an early childhood child psychiatry unit - Ribeiro,Catarina Garcia (2021)
Abstract Introduction: Perceived parental self-efficacy (PSE) has shown an association with positive parental behavior, highlighting its benefit in promoting child well-being and healthy development. The identification of its potential determinants remains a focus of attention in mental health when assessing parental perceptions and cognitions or planning parental interventions. Material/Methods: This was a cross-sectional study in an Early Childhood Child Psychiatry Unit. All parents of babies and toddlers assessed for the first time were included and completed a Parenting Sense of Competence (PSOC) scale (portuguese translation, α= 0.75-0.83) and two additional questions concerning perceptions of support from the other parent and family of origin. Average PSOC was compared between both parents and correlations with perceptions of support were tested. Statistical analysis was conducted in SPSS® version 21 through descriptive analysis and variable correlation (t-test and Pearson r). Results: A total of thirty-four questionnaires were completed. Average PSOC was similar between father and mothers (73.44 vs 72.24, p=0.533). Fathers perceived themselves as more supported than mothers, either from the family of origin (5.09 vs 4.21, p=0.001), as from the other parent (4.91 vs 4.09, p=0.011). A positive correlation was found between father’s PSOC and perception of support from the family of origin (r=0.639, p <0.01). Conclusions: Among mothers of children followed in this Child Psychiatry Unit, support perceptions did not correlate with perceived parental self-efficacy. However, father’s perceived self-efficacy could relate to perceptions of support, raising clinical attention on how fathers and their family of origin can influence the relational triad. Perceptions of parental support should be explored when considering within-family horizontal relations as a potential mechanism influencing vertical relations through its association with perceived self-efficacy.